Production systems, genetic diversity and genes associated with prolificacy and milk production in indigenous goats of sub-Saharan Africa: A Review - Baenyi, S.P.; Junga, J.O.; Tiambo, Christian K.; Birindwa, A.B.; Karume, K.; Mekuriaw, Getinet; Ochieng, J.W. (Scientific Research Publishing, Inc., 2020)
Goats are one of the oldest domesticated animal species widely distributed in the world playing an important role in the food production system in Sub-Saharan African Region (SSAR). Due to their multiple uses (milk production, meat, fiber and hides) and adaptation aptitudes to ecological conditions, goats produce and contribute positively to farmers' socio-economy status in various production systems. This review aimed at giving a summary overview on the goat's production systems characteristics, the genetic diversity and the candidate genes affecting reproductive and milk production performances in goat breeds in SSAR. It has been observed that traditional livestock production system with communal grazing system is the most used in goat keeping in SSAR. The geographical locations play an important role in the relationships between goat's distributions in the region. At the same time, goats might have been differentiated and isolated one to others due to the wide geographic range, the diversify climate and the topography in the region. Among the six worldwide known haplogroups of goat (A, B, C, D, G and F), haplogroup A is the most representative in SSAR. However, haplogroup G and B can be found in some goat populations in some countries in east (Kenya and Ethiopia) and south parts of Africa. This review reveals that little is known on the candidate genes associated with prolificacy and milk production traits in indigenous goat breeds in the region. That observation suggests the importance of assessing candidate genes associated with economic traits in the populations of goat in SSAR.